Mary French Sheldon papers - Sheldon, Mary French, 1847-1936.; Flaubert, Gustave, 1821-1880.
Correspondence, writings, lectures, notes, address book, clippings, scrapbooks, photographs, and other papers primarily concerning Sheldon's interest in Africa, particularly the Belgian Congo (later the Democratic Republic of Congo). Includes fictional writings, translations of works including Salammbo by Gustave Flaubert, and an unpublished work relating to the Congo. Correspondents include Henry M. Stanley; Albert I, King of the Belgians; and several of Albert's cabinet ministers.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Smithsonian Institution.
Author, lecturer, and explorer. Also known as May French Sheldon.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Albert -- I, -- King of the Belgians, -- 1875-1934 -- Correspondence; Stanley, Henry M. -- 1841-1904 -- Correspondence; Africa -- Description and travel; Congo (Democratic Republic) -- Description and travel; Authors; Explorers; Lecturers